Constructivist Philosophy of Student-Centred Learning Approach in Indonesian Higher Education Context - Maulana, Angga; Syihabuddin (IKIP Siliwangi, 2025)
With an emphasis on the educational process in the setting of higher education, this research investigates the constructivist philosophy in the application of the student-centered learning (SCL) approach and the advantages and difficulties of applying constructivist theory to the SCL approach. This study applied a descriptive qualitative study. This study uses classroom observations and interviews conducted in a variety of teaching situations at a private institution in Bandung, Indonesia. According to the results, the majority of the teaching and learning process incorporates elements of constructivist philosophy, particularly the role of the lecturer, learner autonomy, active and collaborative learning, technology usage, assessment approachs, and knowledge production. It encourages more critical thinking, guided interactive learning experiences, and generally improves students’ engagement. The value of this research lies in the development and enhancement discourse on pedagogical approaches at higher education level, especially for an Indonesian situation where it may provide a significant approach to develop learning from constructivist perspective. However, the implementation of SCL faces several challenges, including differences in students’ readiness for self-directed learning directions and resistance to conventional pedagogy from some lecturers.